Creating a Healthy Workplace in a Private Hospital: A Focus on Nursing and Job Satisfaction - Firmanda, Giovanni Iga; Wahyuningsih, Aries (Babali Publisher, 2025)
Introduction: A healthy working environment (HWE) is essential for nurse well-being, job satisfaction, and overall healthcare quality. However, in Indonesia, the conditions of the work environment and the implementation of professional nursing practices in private hospitals remain underexplored. This scoping review aims to identify, evaluate, and propose strategies for improving HWE in private hospitals. Method: A total of 14 studies met the inclusion criteria and were analyzed from ProQuest, NCBI, CINAHL, and SpringerLink from 2013 to 2023. Three major themes emerged: Organizational Support – Policies ensuring nurse welfare, workplace safety, and professional development significantly reduce burnout and enhance job satisfaction. Fair compensation, performance assessments, human resource fulfillment, and nurse engagement in decision-making contribute to a more sustainable work environment; Management and Teamwork – Effective communication, strong leadership, and collaboration are crucial in improving nurse performance and motivation. Hospitals that emphasize nurse-physician cooperation and conflict resolution report higher retention rates and improved patient outcomes; Individual Factors – Workplace relationships, personal resilience, and professional recognition directly affect nurses' mental well-being and job commitment. However, verbal harassment, workplace violence, seniority-based discrimination, and lack of engagement opportunities negatively impact nurse retention. Result: The findings confirm that a strong HWE enhances nurse satisfaction, retention, and patient care quality. Therefore, creating and maintaining a positive work environment requires joint efforts from hospital administrators, policymakers, and healthcare professionals. Conclusion: Future strategies should prioritize comprehensive assessments, communication skills training, ethical practice reinforcement, and continuous professional development to support nurse well-being and optimize healthcare services.